2023
DOI: 10.21203/rs.3.rs-1827631/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Artefactual source of 2-hydroxypyridine

Abstract: As part of the revisions of our original manuscript, we performed 13C-labelling experiments with cultures of the microorganism most strongly correlated with 2-hydroxypyridine (2-HP), i.e. the archaeal species Methanobrevibacter smithii. Although unlabelled 2-HP was detected in the cultures, the measurements by gas chromatography-mass spectrometry (GC-MS) indicated that M. smithii was not the direct source of 2-HP as labelled 2-HP was not measured. Further experiments involving a labelled solvent (deuterated py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Further, this compound is a key molecule in disease pathogenesis and may indicate a causal role of M. smithii in Parkinson’s Disease. However, recent additional analyses by indicated that M. smithii was not the direct source of 2-hydroxypyridine and, as such, further validation is required to determine if M. smithii can produce this compound in vivo ( Wilmes et al, 2023 ). Adults with asthma were also found to have a reduction in M. smithii compared to control subjects ( Wang et al, 2018 ).…”
Section: Human-associated Methanogensmentioning
confidence: 99%
“…Further, this compound is a key molecule in disease pathogenesis and may indicate a causal role of M. smithii in Parkinson’s Disease. However, recent additional analyses by indicated that M. smithii was not the direct source of 2-hydroxypyridine and, as such, further validation is required to determine if M. smithii can produce this compound in vivo ( Wilmes et al, 2023 ). Adults with asthma were also found to have a reduction in M. smithii compared to control subjects ( Wang et al, 2018 ).…”
Section: Human-associated Methanogensmentioning
confidence: 99%